Correlation between Knowledge and Attitudes to the Behavior of Personal Hygiene Food Handlers in Nutrient Department - Hardiah, Muayanah; Nabawiyah, Hafidhotun; Pibriyanti, Kartika (Program Studi Gizi Jurusan Ilmu Kesehatan Masyarakat Fakultas Ilmu Keolahragaan Universitas Negeri Semarang (UNNES) bekerjasama dengan Persatuan Ahli Gizi (PERSAGI), 2020)
Personal hygiene food handlers of processing food at the hospital nutrition department is very important to control the quality of patient food, to improve patient condition. This is because the presence of good hygiene behavior can reduce the risk of contamination in food. Personal hygiene behavior can be influenced by knowledge and attitude. Some factors to determine the prevalence of congenital diseases in food are the lack of knowledge of food handlers and the inattention to apply hygiene when processing food. The purpose of this study was to determine the correlation between knowledge and attitudes towards personal hygiene behavior food handlers in nutrition department of UNS Hospital Surakarta. This type of research was quantitative observation with cross sectional research design. The total population was all food processing workers in Nutrition Department of the UNS Hospital of Surakarta with a total of 22 people. Knowledge and attitude data were obtained by using questionnaire wether behavior data was collected by using a checklist form. Data was analysed using Chi Square test. The results showing the dominant gender of the study is female at 59,1%, then the highest age group is adult at 68,2%, the highest level of education was SMA /SMK 81,8%, the length working time was more than 2 years at 54,5% and the income range is 1.000.000-2.000.000. The level of good food handlers knowledge is 81,8%, good food handlers attitude is 72,7% and good food handlers behavior is 59,1%. Based on statistical tests the results showed that there was no correlation between knowledge and personal hygiene behavior of food handlers p = 1,000 and there was no correlation between attitudes and personal hygiene behavior of food handlers p = 0,178.